Temperature and Humidity Monitoring on IoT Based Shipment Tracking - Zaenur Rohman (Journal of Telematics and Informatics, 2018)
To maintain quality of goods among shipment process, monitoring and controlling is performed. Moreover, position of the vehicles is performed by GPS tracking. However, conventional monitoring and controlling temperature and humidity is done manually.  Moreover, inaccurate measurement during shipment process is affected to the goods quaity especially for goods and beverages packets. Inaccurate tracking has contributed as one factor which causes vehicle lost in control. To addressing these limitation, integrating shipment process such as temperature, humidity, tracking and tracking system are proposed based on Internet of Things (IoT). The systems are conducted by uses Arduino Uno, RFID MFRC522, GPS Neo6M, DHT11 dan RTC DS1307. The system performance has monitored humidity and temperature properly and bus range tracking system is conducted using Neo6M based on IoT. Data measurement result are delivered onto Clouduino over Internet network at any time. Therefore realtime measurement and tracking are visualized onto Web using API Google Maps. The performance result shows that within two experiment treatments, such as static and mobility measurements, the propose system are performed well. In static measurements, the average interval value of the data transmission time is 5,75 seconds from the designed interval value of 5 seconds, the average value of the deviation from the interval of data transmission time is 0,75 seconds, and the average delay time between data transmission and reception is 0,3 seconds. While at dinamic measurements, the average interval value of the data transmission time is 6.22 seconds from the designed interval value of 5 seconds, the average value of the deviation from the interval of data transmission time is 1.22 seconds, and the average delay time between data transmission and reception is 2.31 seconds.